Emily of New Moon [compact disc, unabridged] - Montgomery, L. M. (Lucy Maud), 1874-1942 (Blackstone Audio Books, 1998)
When Emily's father dies, leaving her an orphan, she is sent to live with a stern aunt in Prince Edward Island, where her resourcefulness and love of writing help her adjust to a new way of life.